Period piece - Raverat, Gwen (University of Michigan Press, 1991)
Originally published: New York : Norton, 1976.; At the close of 1952, Bettrand Russell wrote to Gwen Raverat that he had been reading Period Piece â€œwith the very greatest delight.â€ Raveratâ€™s memories of childhood and coming of age during the final years of Victoriaâ€™s reign capture a young womanâ€™s impressions of dons, eccentrics, and tradespeople in Cambridge during the 1890s. With astonishing power Period Piece brings us into the real presence of the late Victorian past